2016
DOI: 10.4103/0972-2327.176857
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice in relation to stroke: A community-based study from Kolkata, West Bengal, India

Abstract: Background:The rising incidence of stroke in India indicates the importance of evaluating the existing knowledge, attitude, and practice (KAP) in the community, which is essential for stroke control.Objective:To explore and compare stroke-related KAP among participants from stroke-affected families (SAFs) and nonstroke-affected families (NSFs).Design:Using stratified random sampling, a three-phase house-to-house survey was conducted in Kolkata, West Bengal, India. First, field investigators screened subjects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 23 publications
1
23
1
1
Order By: Relevance
“…Strangely the knowledge of risk factors was low among the families affected with stroke. 8 The findings in the above discussed studies are similar to that observed among anganwadi workers before training in our study. National programme for prevention and control of Cancer, Diabetes, CVD and Stroke (NPCDCS) aims at integration of NCD interventions in the National Rural Health Mission framework for optimization of scarce resources and provision of seamless services to the end customer /patients as also for ensuring long term sustainability of interventions.…”
Section: Discussionsupporting
confidence: 90%
“…Strangely the knowledge of risk factors was low among the families affected with stroke. 8 The findings in the above discussed studies are similar to that observed among anganwadi workers before training in our study. National programme for prevention and control of Cancer, Diabetes, CVD and Stroke (NPCDCS) aims at integration of NCD interventions in the National Rural Health Mission framework for optimization of scarce resources and provision of seamless services to the end customer /patients as also for ensuring long term sustainability of interventions.…”
Section: Discussionsupporting
confidence: 90%
“…This observation was consistent with other studies. 5,6,8,[14][15][16][19][20][21][22] Smoking was the most common risk factor identified in studies from Iran 8 and Australia. 18 Unhealthy dietary practice was most commonly recognised as a risk factor in a study from Iraq.…”
Section: Discussionmentioning
confidence: 99%
“…6 Individuals who fulfilled the selection criteria were included to the study after obtaining a written informed consent. The investigators then administered the questionnaire to the subjects through a face-to-face interview.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ironically, SAF group had lesser knowledge of the risk factors such as diabetes (P < 0.001), smoking (P < 0.014), alcoholism (P < 0.0001), family history (P < 0.0001), and mild stroke symptoms such as headache, (P < 0.001), vomiting (P < 0.001), and fits (P = 0.003) as compared to the NSAF group. [21] Even in regions where thrombolysis is available not all patients are able to benefit from the facility. In a study that was done in tertiary care center with a stroke unit in Bengaluru, 100 consecutive patients who were candidates for thrombolysis but were not thromobolysed for various reasons were evaluated.…”
Section: Present Scenario Of Stroke Carementioning
confidence: 99%